Effect of livestock stocking rate on fatty acid and tocol composition of milk from sheep managed under part-time grazing - Bravo-Lamas L.; Bustamante M.A.; Aldai N.; Nájera A.I.; Mandaluniz N.; Barrón L.J.R. (Innovation for sustainability in sheep and goats, 2019)
Dairy sheep management system in the Basque Country (northern Spain) is based predominantly on part-time grazing from late winter to early summer. The milk produced is primarily used for cheesemaking and having high nutritional quality milk at the lowest cost possible is important for cheese makers. Intensification of the system can have strong influence on farm profitability, environment, and milk and cheese quality. The aim of the present work was to investigate the effect of sheep stocking rate managed under parttime grazing on milk quality measured as fatty acid (FA) and tocol (TC) composition. Two homogeneous groups of 60 ewes each grazed on the same paddocks divided at high (H) and low (L) stocking rate, respectively. Bulk milk samples were taken once a month from mid-April to June. TC profile of milk samples was similar in both groups of animals over the sampling period although the highest contents of the major TC (α-tocopherol; mg/100 DM) were found in samples collected in June. Changes in the FA content (g FA/100 g milk fat) affected by stocking density were mainly observed in the unsaturated FA fraction. Samples from L group showed higher content than H group of α-linolenic (18:3n-3) and associated rumen biohydrogenation intermediates as rumenic (9c,11t-18:2) and vaccenic (11t-18:1) which are considered beneficial for human health. Changes in diet due to stocking rate seemed to be linked to differences in the milk FA composition.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)